Supervision in Inclusive Islamic Early Childhood Education: Strategies Approach for an Integrated Program - Awaludin, Dandy Prasetyo; Sintya, Tira Fitria Astrid Dhica; Purwanto, Nurtanio Agus; Hermanto, Hermanto (Ta'dib, 2024)
The implementation of supervision in the field of education does not only focus on evaluation or assessment of weaknesses but rather on efforts to improve the quality of education. Supervision in early childhood education that implements inclusive programs needs to be continuously developed to adjust to the learning environment in schools. This study aims to describe the strategy for developing inclusive education supervision in integrated one-roof Islamic early childhood education institutions in Pati Regency. This study uses a qualitative method with a case study approach. The source of research data was obtained from informants of three school principals from each early childhood education service unit, namely TPA, KB, and TK. Data collection techniques include observation, interviews, and documentation. The data analysis process is carried out inductively by detailing empirical facts through direct activities in the field. The results of the study indicate that in integrated Islamic-based inclusive early childhood education institutions, educational supervision and coaching programs have been implemented by all teachers and school education personnel. The strategy for developing educational supervision that can be applied forms a solid foundation for optimizing inclusive learning practices. These strategies include an in-depth understanding of inclusion, teacher involvement and training, development of inclusive learning plans, utilization of resources, and continuous monitoring and evaluation. Overall, these findings continue to emphasize the inclusion program promoted by the institution.